Edukasi Dan Konseling Terhadap Tingkat Stres Pada Ibu Hamil Dalam Menghadapi Persalinan - Manuntungi, Andi Ernawati; Musdalifah, Musdalifah; Rabuana, Susi; Thalib, Kiki Uniatri (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Anxiety is a feeling of fear that is unclear and not supported by the situation. Individuals who feel anxious will feel uncomfortable or afraid, but do not know the reason why this condition occurs. The aim of community service activities is to educate pregnant women who are anxious about the normal delivery process and to be able to increase the level of knowledge and skills of pregnant women as an effort to improve health during pregnancy. The method used in this community service activity is to carry out community service activities by providing material starting with a pre-test and post-test. These results indicate that there are differences in the level of knowledge before and after mentoring activities. Cadre optimization activities in pregnant women's classes are quite effective in increasing the level of knowledge as an effort to improve health during pregnancy. The conclusion is that this community service activity is to assist pregnant women who experience stress and anxiety in facing childbirth continuously and sustainably, to accompany and guide pregnant women in efforts to improve their health during pregnancy.